Apoyo ingenieril en los diferentes proyectos establecidos por la alcaldía y planeación del municipio de Gámeza, Boyacá - Botia Fagua, Juan Diego (Universidad Antonio Nariño, 2022)
In the internship of a university student, it is sought that he/she supports and acquires new knowledge, taking into account that he collaborates with the supervision and verification of the different projects proposed in advance, taking into account the progress in the works that will be developed throughout his time at the same, as well as some that were already underway, he will help with the preparation of different budgets for the design and execution of new projects that benefit the Gamecense community, taking into account that they favor the economy of the region, taking into account the welfare of the community. As it will be carried out in a public entity, such as the municipal mayor's office and planning secretary of Gámeza - Boyacá, this internship can bring benefits to the intern, since he would have work experience that contributes to his curriculum.